Perovskite X‐Ray Detectors: Flexible, Printable Soft‐X‐Ray Detectors Based on All‐Inorganic Perovskite Quantum Dots (Adv. Mater. 30/2019). Issue 30 (23rd July 2019) - Liu, Jingying; Shabbir, Babar; Wang, Chujie; Wan, Tao; Ou, Qingdong; Yu, Pei; Tadich, Anton; Jiao, Xuechen; Chu, Dewei; Qi, Dongchen; Li, Dabing; Kan, Ruifeng; et al.
Abstract : In article number1901644, Babar Shabbir, Yupeng Zhang, Qiaoliang Bao, and co‐workers utilize inexpensive inkjet printing to homogeneously print a perovskite film consisting of all‐inorganic halide perovskite quantum dots on various substrates, which they further develop into an X‐ray detector. This type of detector is an ideal candidate for applications in soft/hard X‐ray detection and large‐area flat/flexible imaging technologies.